Outcomes of patients with chronic myelomonocytic leukaemia treated with non-curative therapies: a retrospective cohort study. Issue 2 (February 2021) - Pleyer, Lisa; Leisch, Michael; Kourakli, Alexandra; Padron, Eric; Maciejewski, Jaroslaw Pawel; Xicoy Cirici, Blanca; Kaivers, Jennifer; Ungerstedt, Johanna; Heibl, Sonja; Patiou, Peristera; Hunter, Anthony Michael; Mora, Elvira; et al.
Summary: Background: Approval of hypomethylating agents in patients with chronic myelomonocytic leukaemia is based on trials done in patients with myelodysplastic syndromes. We aimed to investigate whether hypomethylating agents provide a benefit in subgroups of patients with chronic myelomonocytic leukaemia compared with other treatments. Methods: For this retrospective cohort study, data were retrieved between Nov 30, 2017, and Jan 5, 2019, from 38 centres in the USA and Europe. We included non-selected, consecutive patients diagnosed with chronic myelomonocytic leukaemia, who received chronic myelomonocytic leukaemia-directed therapy. Patients with acute myeloid leukaemia according to 2016 WHO criteria at initial diagnosis (ie, ≥20% blasts in the bone marrow or peripheral blood) or with unavailability of treatment data were excluded. Outcomes assessed included overall survival, time to next treatment, and time to transformation to acute myeloid leukaemia. Analyses were adjusted by age, sex, platelet count, and Chronic myelomonocytic leukaemia-Specific Prognostic Scoring System (CPSS). Patients were grouped by first received treatment with either hydroxyurea, hypomethylating agents, or intensive chemotherapy, and stratified by risk according to blast count, French-American-British subtype, CPSS, WHO 2016 subtype, and the eligibility criteria of the DACOTA trial (NCT02214407 ). Findings: 949 patients diagnosed with chronic myelomonocytic leukaemia between April 13, 1981, and Oct 26, 2018, were included. Median follow-up was 23·4 months (IQR 11·5–42·3) from diagnosis and 16·2 months (6·6–31·6) from start of first-line treatment. 412 (43%) of 949 patients received hypomethylating agents as first treatment, 391 (41%) hydroxyurea, and 83 (9%) intensive chemotherapy. Adjusted median overall survival for patients treated with hydroxyurea versus hypomethylating agents was 15·6 months (95% CI 13·1–17·3) versus 20·7 months (17·9–23·4); hazard ratio (HR) 1·39 (1·17–1·65; p=0·0002) and 14·0 months (9·8–17·2) versus 20·7 months (17·9–23·4; HR 1·55 [1·16–2·05]; p=0·0027) for those treated with intensive chemotherapy versus hypomethylating agents. In patients with myeloproliferative chronic myelomonocytic leukaemia (myeloproliferative CMML), median overall survival was 12·6 months (10·7–15·0) versus 17·6 months (14·8–21·5; HR 1·38 [1·12–1·70]; p=0·0027) for patients treated with hydroxyurea versus hypomethylating agents, and 12·3 months (8·4–16·6) versus 17·6 months (14·8–21·5; HR 1·44 [1·02–2·03]; p=0·040) for intensive chemotherapy versus hypomethylating agents. Hypomethylating agents did not confer an overall survival advantage for patients classified as having lower-risk disease (ie, myelodysplastic chronic myelomonocytic leukaemia with <10% blasts, CMML-0, or lower-risk CPSS). Interpretation: These data suggest hypomethylating agents as the preferred therapy for patients with higher-risk chronic myelomonocytic leukaemia and those with myeloproliferative CMML. Our findings also suggest that CPSS is a valuable tool to identify patients who are most likely to benefit from hypomethylating agents. Further evidence from prospective cohorts would be desirable. Funding: The Austrian Group for Medical Tumor Therapy.